Utilization of organic waste and soil microorganisms in compost making and its application in hybrid corn cultivation in the middle school environment in Medan City - Muhdi; Sofia Hanafiah, Diana (Talenta Publisher, 2019)
The existence of educational institutions is very important and strategic to educate a quality generation. The target of this service program is junior high school in Medan, namely MTs P.P. Raudhatul Hasanah at the Ar-Raudlatul Hasanah Islamic Boarding School in Medan. Waste management and utilization and through the provision of soil microorganisms into compost and its role in land use through hybrid maize cultivation in the MTs P.P. school environment. Raudhatul Hasanah .. In addition, the need for the application of hybrid maize cultivation in the MTs P.P. school environment. Raudhatul Hasanah. Availability of organic waste treatment facilities as a means to process waste into compost. In addition, the USU PPM proposing team will provide multipurpose bins for the MTs P.P. school environment. Raudhatul Hasanah. The proposing team will practice compost processing and safeguarding hybrid corn in the school area. It is expected that later it will provide good direct benefits in the form of good food crops in the form of indirect benefits as knowledge and practice of MTs P.P. students. Raudhatul Hasanah. Partner involvement through community service programs by the community service team of MTs students. P.P. Raudhatul Hasanah is very high. This is indicated by the willingness of MTs school students. P.P. Raudhatul Hasanah was very enthusiastic and the active participation of students who attended the program was very satisfying. In addition this activity also helps MTs school students. P.P. Raudhatul Hasanah in studying and knowing waste management and its use through counseling and demonstrations. The success of the program in schools in MTs P.P. Raudhatul Hasanah Medan is largely determined by the participation of partners at each stage of the activities carried out. Partners namely schools in MTs P.P. Raudhatul Hasanah Medan really helped the implementation of community service programs in the USU community.